Perancangan Interior Japanese Action Figure Center di Surabaya - Christoforus Handy; Cok Gede Padmanaba; Diana Thamrin (Intra, 2015)
Japanese Action Figure Center in Surabaya is intended for lovers of action figures to be able to buy , assemble , and respond to their needs to provide a place that has the style of anime in Surabaya . The concept of this design is stylish and modern techno , which impressed futuristic design , and followed by the use of advanced technology in order to access the facilities in place . Brand image of the product sold itself is